Comparison of 2-D and 3-D Diode-Pumped Solid-State Laser Cooling Models - Dabulytė, J.; Ivanauskas, F. (Nonlinear Analysis: Modelling and Control, 2003)
We propose a cooler of a laser material which compensates the thermal gradients caused by the pump radiation by the gradients created by the cooler. The mathematical model of the system is based on the numerical solution of the heat transfer equation using a finite - difference technique. The 3-D and 2-D computer simulations were used to investigate the cooling problem and show the reliability of two-dimensional model.
Keywords: diode-pumped solid-state laser; Yb:KGW; laser cooling system; thermal effects